Teen dating violence in Croatia : Prevalence, predictors and prevention - Löw Stanić, Ajana (2013)
The project Prevention of teen dating violence through education system in Croatia includes an extensive research on teen dating violence and the large-scale set of preventive workshops for secondary school students. Prevalence of teen dating violence and some related concepts were assessed on 1225 secondary schools students throughout Croatia. The results showed a high prevalence of dating violence, with above 80% of participants reporting to have experienced or perpetrated a violent behaviour in a relationship. Furthermore, it was found that females have more accurate beliefs about relationships, upholding own rights in a relationship is more important to them, they are more keen to keep own boundaries and are also more likely to seek and provide help in case of dating violence than males. They reported perpetrating psychological and physical violence more often and being less often victimized than did males, which is consistent with new research findings on adolescents in the United States. Sexual violence was reported least often with no gender differences in victimization and perpetration. Male gender, inaccurate beliefs about relationships and higher importance of own rights predicted more frequent victimization, while longer duration of the relationship, inaccurate beliefs about relationships, past victimization, higher importance of own rights and poorer recognition of violent behaviors predicted more frequent perpetration of violence. The large-scale preventive workshops were delivered to 5150 secondary school students in Croatia. 4 interactive workshops of 45 minutes each addressed these relationships topics: beliefs about healthy and safe relationship, recognition of violence in youth relationships, knowledge about own rights, awareness of own victimization and perpetration of violence, setting boundaries and seeking and providing help in case of violence in a relationship. The effectiveness of the workshops was evaluated on a sample of 1587 adolescents (829 students in the intervention condition and 758 in the comparative group of classes). Four to 6 months after the workshops delivery, the participants in the intervention classes reported statistically significant improvements: perpetrating and experiencing less violent behaviors, improved beliefs about healthy and quality relationship, better recognition of violent behaviors and knowledge of rights in a relationship. The preventive program with only four one-hour workshops delivered to secondary school students is effective in reducing violence in teen romantic relationships and improving related risk-reducing factors.